1, 25-Dihydroxyvitamin D3 regulates expression of LRP1 and RAGE in vitro and in vivo, enhancing Aβ1–40 brain-to-blood efflux and peripheral uptake transport. (13th May 2016) - Guo, Y.-X.; He, L.-Y.; Zhang, M.; Wang, F.; Liu, F.; Peng, W.-X.
Highlights: 1, 25(OH)2 D3 enhanced Aβ1–40 brain-to-blood efflux by upregulating LRP1 expression in bEnd.3 cells under hypoxia and mice. 1, 25(OH)2 D3 reduced Aβ1–40 blood-to-brain influx by downregulating RAGE expression in bEnd.3 cells under hypoxia. 1, 25(OH)2 D3 increased Aβ1–40 peripheral uptake by upregulating LRP1 expression in HepG2 cells. 1, 25(OH)2 D3 upregulated VDR expression in mice hippocampus, bEnd.3 cells under hypoxia and HepG2 cells. Abstract: Alzheimer's disease (AD) is characterized by the accumulation and deposition of plaques of amyloid-β (Aβ) peptide in the brain. Growing epidemiological and experimental studies have shown that 1, 25-dihydroxyvitamin D3 (1, 25(OH)2 D3 ) exerts neuroprotection against AD. However, the underlying mechanisms of the action remain unclear. Since Aβ clearance plays a crucial role in Aβ balance in the brain, the aim of the present study was to investigate potential effects of 1, 25(OH)2 D3 on Aβ1–40, the major soluble oligomeric form of Aβ, clearance via transport across blood–brain barrier (BBB) mediated by low-density lipoprotein receptor-related protein 1 (LRP1) (efflux) and receptor for advanced glycation end products (RAGE) (influx) and peripheral uptake by liver mediated by LRP1. We identified colocalization of LRP1 and RAGE at BBB of mice, established an in vitro BBB model by culturing monolayer mouse brain microvascular endothelial cell line (bEnd.3) cells under hypoxia and observed that 1, 25(OH)2 D3 treatment enhanced Aβ1–40 efflux across the BBB model and uptake by HepG2 cells. After 1, 25(OH)2 D3 exposure, LRP1 expression was increased significantly both in vivo and in vitro, and RAGE expression was reduced in the in vitro BBB model but not in microvascular endothelial cells of mice hippocampus. Additionally, we explored the correlation between the corresponding effects of 1, 25(OH)2 D3 and its nuclear hormone receptor vitamin D receptor (VDR) level. We found that VDR expression was upregulated after 1, 25(OH)2 D3 treatment both in vivo and in vitro . Collectively, our finding that 1, 25(OH)2 D3 reduces cerebral Aβ1–40 level by increasing Aβ1–40 brain-to-blood efflux and peripheral uptake through regulating LRP1 and RAGE could shed light on the mechanism of 1, 25(OH)2 D3 neuroprotection against AD. And the action of 1, 25(OH)2 D3 might be associated with the VDR pathway.